Changements de la structure sociale de la Pologne rurale entre 1991 et 2015 - Halamska, Maria (Sociologie des mondes ruraux en Pologne et en France : terrains et études, 2024)
The article presents changes in the socio-occupational structure of rural Poland over the period of 25 years (1990‒2015), which includes the post-communist transformation and the first decade of its membership in the European Union. During this period, major changes took place in the rural social structure, predominantly as a result of the following three processes: 1. depeasantization / desagrarianization, due to which the share of farmers decreased from 46% to 26%, which means they lost their dominant position in the social structure of Polish villages, 2. proletarianization, as a result to which the share of laborers increased from 33% to 45%, which means that they became the dominant socio-occupational group in rural areas, 3. bourgeoization, i.e. an increase in the share of representatives of occupational groups representing the middle class from 15% to 28%, due to which it became a significant social actor in rural areas. Those processes occurred with divergent dynamics; what is noteworthy here is the pace of bourgeoization/gentrification and depeasantization/desagrarianization. The pace of change was faster during the post-communist transformation. It was territorially diversified which resulted in creation of various local types of social structure. Changes in the social structure in this period took place in line with the universal pattern of developed Western countries, and their specificity lies in simultaneous rather than successive occurrence of these processes. The empirical base is data from representative sociological studies (grouping of occupations according to ISCO-08 classification): Polish General Social Survey for 1992 and Social Diagnosis for 2003 and 2015.